Implementation Model Quality Management System (IQMS) and Model Participatory Rural Appraisal (PRA) to Increase Performance Small and Medium Enterprise (SMEs) in Dili-Timor Leste - Benjamin, Tito Mau Pelu; Nindhia , Tjokorda Gde Tirta; Priambadi, I.G.N.; Adnyana , I.W. Bandem (International Journal of Membrane Science and Technology, 2023)
The research carried out by researchers was motivated by three things: (1) Implementation of the Quality Management System (IQMS) Model in small and medium industries in order to improve the quality of the products produced to truly compete in marketing both in local and global markets; (2) Participatory Rural Appraisal (PRA) model to empower regional communities in advancing regional small and medium industries involving community social institutions and Tais weaving groups, to support the Ministério do Comércio, Turismo e Indústria (MCTI) program, this is NGO Masin Roman Mundu (MAROMUN) (2006) has conducted research and identified the potential for SMEs to be established. The PRA method is important for regional communities in empowering regional industry as a disruptor for Small and Medium Industries. (3) The company’s performance of small and medium industries (KIKM) must be carefully considered so that it can encourage employees to advance small and medium industries in Timor Leste. The research method used is qualitative and quantitative using questionnaires which can later be made according to the agreement of researchers and institutions. social community who work in the company in filling out the questionnaire created by the researcher. The results of the research show that the IQMS model, PRA model and small and medium industrial performance can improve quality and empower the community in: (1) Improving the quality of products produced based on ISO 9001:2015; (2) Involving the community in increasing the productivity of regional small and medium industries based on available raw materials; (3) Increasing the work performance of small and medium industries is very important in the progress of companies; (4) increasing the productivity of small and medium industries is the most important thing for manufacturing companies in their industrial processes. Based on these four results, four (novelties) were found, namely: (1) Product quality based on ISO 9001;2015; (2) Create a priority matrix for small and medium industrial activities developed based on opinion polls on the Supplier interface (I/F), Top Down interface (I/F), Community interface (I/F) and interface (I/F). ) Customers are built according to the order of values ??starting from the largest to the order of smallest values, (3) The results of the research can increase production productivity based on the time that has been set up by the company leadership. (4) Production process activities can be improved based on materials and raw materials that have been provided by the company as a breakthrough and increase the productivity of Small and Medium Industries to achieve consumer satisfaction with the products produced by implementing the Quality Management system model (IQMS) and the participatory rural appraisal (PRA) model to measure performance through empowering small and medium industries as supporters of large industries.